Echotexture of recurrent laryngeal nerves: the depiction of recurrent laryngeal nerves at high-frequency ultrasound during radical thyroidectomy - Hu, Ziyue; Lu, Man; Jiang, Zirui; Wang, Xu; Yang, Wei; Fan, Yuting; Li, Tingting; Wang, Lu; Wei, Ting; Dai, Quan (Frontiers in Endocrinology, 2024)
Introduction: To investigate the ultrasound characteristics of recurrent laryngeal nerves (RLNs) during radical surgery for thyroid cancer and to enhance the understanding of RLN ultrasound features. Methods: From October 2021 to December 2022, a prospective study was conducted involving 24 patients scheduled for bilateral thyroid surgery. Near the conclusion of the surgery, intraoperative ultrasonography of the RLN within the tracheoesophageal groove was performed using a 15-7 MHz transducer. The thickness and width of the RLN were measured during the procedure. Results: The internal architecture of the RLN was observed to consist of multiple hypoechoic, parallel, but discontinuous linear hyperechoic areas separated by bands. In the normal RLN group, the diameter of the RLN was relatively consistent, with thickness ranging from 2.20 to 2.71 mm (mean: 2.48±0.14 mm) and width from 1.25 to 1.70 mm (mean: 1.45±0.11 mm). Both weight and the body mass index (BMI) showed a statistically significant correlation with RLN thickness (Weight: r=0.544, P=0.001; BMI: r=0.605, P=0.001). The BMI also showed a statistically significant correlation with the RLN width (r=0.377, P=0.033). In the RLN invasion group, the width of invaded RLNs ranged from 1.9 to 2.3 mm (mean: 2.10±0.11 mm), while the width of non-invaded RLNs ranged from 2.6 to 3.2 mm (mean: 2.93±0.20 mm). Conclusions: Ultrasound effectively reveals the structural features of the RLN and enhances sonographers' understanding of RLN characteristics.